RISK FACTORS FOR PHYSICAL DISABILITY IN PATIENTS WITH LEPROSY: A SYSTEMATIC REVIEW - Winona Iriadi, Felicia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Leprosy is also referred to as Hansen disease. It is a chronic granulomatous infection generally caused by Mycobacterium leprae and Mycobacterium lepromatosis, both of which primarily affects the skin and peripheral nerves. Physical disability (PD) can occur before leprosy diagnosis, during treatment and post-release from treatment. However, although patients may be exposed to risk factors that potentiate the risk of more severe PD they stop being routinely evaluated once the treatment of active leprosy has been completed. The aim: This study aims to show about risk factor for physical disability in patients with leprosy. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 104 articles, whereas the results of our search on SagePub brought up 77 articles. The results of the search conducted for the last year of 2013 yielded a total 88 articles for PubMed and 48 articles for SagePub. The result from title screening, a total 7 articles for PubMed and 28 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Delayed diagnosis, nerve damage, no skin lesions, WHO and Ridley-Jopling classifications, leprosy reactions, advanced age, rural occupation, Han ethnicity, and male sex were associated with disability in leprosy patients. Identifying risk factors could help to prevent physical disability.